Reduced Carbon Dots versus Oxidized Carbon Dots: Photo‐ and Electrochemiluminescence Investigations for Selected Applications. Issue 20 (22nd March 2013) - Xu, Yang; Wu, Ming; Feng, Xi‐Zeng; Yin, Xue‐Bo; He, Xi‐Wen; Zhang, Yu‐Kui
Abstract The study of the composition, morphology, and surface structure of carbon dots (Cdots) is critical to understanding their effect on the photo‐ and electrochemiluminescence (PL and ECL) of Cdots in selected applications. Herein, two kinds of Cdots were prepared with 3‐(3, 4‐dihydroxyphenyl)‐L‐alanine (L‐DOPA) as precursor. The Cdots prepared by using a carbonization‐extraction strategy have a low oxidation level and are denoted as reduced Cdots (r‐Cdots). The Cdots obtained with a carbonization‐oxidation process are highly oxidized and are denoted as oxidized Cdots (o‐Cdots). The o‐Cdots have a carbon core and oxygen‐containing loose shell, but the r‐Cdots consist mainly of the carbon core. Whereas r‐Cdots have a strong blue PL but no apparent ECL response, o‐Cdots exhibit a relatively weak PL and strong ECL emission. These properties allow for selected applications of the Cdots. The r‐Cdots were used in cell imaging with their high PL emission. The o‐Cdots, with their high ECL efficiencies, were selected to sense Cu2+ with Cu2+‐inducing ECL quenching in the o‐Cdots/K2S2O8 system. This work provides the possibility to control the composition of Cdots for selected applications and shows a good way to characterize surface traps of Cdots because ECL is characterized by the surface‐state and PL is mainly related to the core‐state in Cdots.